Konsep Penyelesaian Perambahan Kawasan Taman Wisata Alam (TWA) Holiday Resort di Kabupaten Labuhan Batu Selatan Provonsi Sumatera Utara - Marisca, Ovien; Widowaty, Yeni (Faculty of Law, University of Ahmad Dahlan, 2018)
The rising population has the potential to increase the need for land, on the other hand faced with the fact that the land is not increased. The most accessible target is forest area. This is what opens up opportunities for forest encroachment. The TWA Holiday Resort Forest area initially includes production forests. Part of the area has been converted into plantation area. To save some of it again, the Minister of Forestry issued Decree No. 695/Kpts-II/1990 which establishes its transition function to TWA (Holiday Resort). The condition of TWA Holiday Resort area is now very worrying. The purpose of this study is to examine, analyze the implementation of forest protection principles in the case of the TWA Holiday Ressort Expansion Area in Labuhan Batu Selatan Regency and to mnyusun Concept of Settlement of TWA Holiday Resort in Labuhan Batu Selatan Regency. The type of research used is empirical juridical consisting of primary data and secondary data. Primary data was conducted with field research at TWA Labuhan Batu Selatan. The result of the research shows that Implementation of forest protection in Labuhan Batu Selatan Regency has not run well because of the lack of firmness of local government apparatus and law enforcement officers in overcoming the encroachment of TWA forest area, so there are still many activities of encroachment done by society even there which established private elementary and junior high schools, village head offices and other buildings. The concept of completing the encroachment of TWA Holiday Resort in the future is to renew the law by improving Law No. 41 of 1999 on forestry, because in article 78 of the Forestry Law the criminal offense starts from letter d, article 78 a, b, and c not mentioned sanctions, In addition to legal reforms, which need to be improved such as law enforcers, the parties that form and apply the law must be good, facilities or facilities that support law enforcement must also be good, the community or the environment in which the law is applied must support, this is so that efforts in tackling the encroachment of TWA area can be more effective.